Transannular reactions of two parallel 1,3-butadiynes: syntheses, structures, and reactions of 1-azacyclotetradeca-3,5,10,12-tetrayne derivatives - Schmidt, Erik M.; Gleiter, Rolf; Rominger, Frank (Chemistry - a European journal, 2003)
The synthesis of 1alkyl and 1aryl-1-azacyclotetradeca-3,5,10,12-tetraynes was achieved in a stepwise approach. The key intermediate was 1,13-dibromotrideca-2,4,9,11-tetrayne (18). Reaction with methyl- (19 a), ethyl- (19 b), isopropyl- (19 c), n-butyl- (19 d), and tert-butylamine (19 e) as well as aniline (19 f) and p-methoxyaniline (19 g) gave the corresponding 14-membered tetraynes 20 a-20 g. The ring inversion process of 20 b was studied by variable temperature 1H NMR spectroscopy. From these measurements a value of 10.6 kcal mol−1 was calculated for ΔG≠. Xray investigations on single crystals of 20 b, 20 c, and 20 f revealed the axial position for the substituent at each nitrogen atom. For 20 b we encountered the chair conformation, for 20 c both chair and boat conformations, and for 20 f the boat conformation in the solid state. The reaction of 20 c with concentrated HCl in ethanol yielded 2,10-dichloro-6-isopropyl-6-azatricyclo[9.3.0.04,8]tetradeca-1(11),2,4(8),9-tetraene (25 c). Compound 25 c was oxidized by 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ) to 27 c. The structure of the latter was confirmed by Xray investigations. The reaction of 20 c in aqueous HCl lead to the formation of 10-chloro-2-isopropyl-1,3,4,6,7,8-hexahydro-2H-benzo[g]isoquinolin-9-one (37 c). The structure of 37 c was verified by Xray studies on single crystals.